2014
DOI: 10.1093/conphys/cou047
|View full text |Cite
|
Sign up to set email alerts
|

A product of its environment: the epaulette shark (Hemiscyllium ocellatum) exhibits physiological tolerance to elevated environmental CO2

Abstract: Ocean acidification is predicted to affect the performance of marine species, but little is known about the effects on sharks. We found that long-term exposure to elevated CO2 did not affect the epaulette shark, possibly because it experiences fluctuating environmental conditions in its shallow coral reef habitat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 60 publications
7
49
0
Order By: Relevance
“…Similar acid-base compensation, blood haematology variables (e.g. haematocrit, haemoglobin concentration, and mean cell haemoglobin concentration) and respiratory (resting oxygen consumption rates, citrate synthase activity and hypoxia tolerance via Pcrit) responses to elevated CO 2 were observed in H. ocellatum [35]. The latter authors suggested that these physiological responses rsbl.royalsocietypublishing.org Biol.…”
Section: Physiologymentioning
confidence: 60%
See 1 more Smart Citation
“…Similar acid-base compensation, blood haematology variables (e.g. haematocrit, haemoglobin concentration, and mean cell haemoglobin concentration) and respiratory (resting oxygen consumption rates, citrate synthase activity and hypoxia tolerance via Pcrit) responses to elevated CO 2 were observed in H. ocellatum [35]. The latter authors suggested that these physiological responses rsbl.royalsocietypublishing.org Biol.…”
Section: Physiologymentioning
confidence: 60%
“…The physiological effects of simulated end-of-century elevated CO 2 conditions have only been evaluated in four relatively sedentary, benthic species: the temperate lesserspotted (Scyliorhinus canicula) catshark [38] and Port Jackson (H. portusjacksoni) sharks [39,40] and the tropical bamboo (C. punctatum) [32][33][34] and epaulette (H. ocellatum) sharks [35,36] (table 1). Previous studies investigating physiological processes under elevated CO 2 in sharks have been conducted at very high CO 2 levels (.8-10 mm Hg, approximately 10 000-13 000 matm) (e.g.…”
Section: Physiologymentioning
confidence: 99%
“…P CO2 between 600 and 2000 µatm). The pattern that emerged was complete regulation of blood plasma pH and a 2-5 mmol l −1 increase in blood plasma [HCO 3 − ] Esbaugh et al, 2016Esbaugh et al, , 2012Green and Jutfelt, 2014;Heinrich et al, 2014;Heuer et al, 2016;Strobel et al, 2012) (Table 1). Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…The pattern that emerged was complete regulation of blood plasma pH and a 2-5 mmol l −1 increase in blood plasma [HCO 3 − ] Esbaugh et al, 2016Esbaugh et al, , 2012Green and Jutfelt, 2014;Heinrich et al, 2014;Heuer et al, 2016;Strobel et al, 2012) (Table 1). Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014). The lack of change in plasma [Cl − ] in marine fish could be due to the difficulty in accurately measuring small changes in [Cl − ] compared with 'background' control levels of 140-200 mmol l −1 (see Genz et al, 2008;Erlacher-Reid et al, 2011;Esbaugh et al, 2016;Lin et al, 2003;Toews et al, 1983;reviewed in Evans et al, 2005).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…Temperature is an important ecological factor, known to have a profound effect on many metabolic processes in aquatic ectotherms, such as fishes (Di Santo and Bennett, 2011a;Fry, 1971;Magnuson et al, 1979). At the same time, although some studies report little to no effect (or even a positive effect) of CO 2 on fishes (see, for example, Green and Jutfelt, 2014;Heinrich et al, 2014;Jutfelt and Hedgärde, 2015;Rummer et al, 2013), several studies have presented data suggesting that increasing ocean acidification has the potential to exert several adverse effects on fish life history traits, such as malformation during skeletogenesis (Chambers et al, 2013), reduced survival (Baumann and Conover, 2011), reduced body condition and increased developmental time , as well as on several other important behavioral and physiological traits, such as alertness, predator avoidance and hunting (Ferrari et al, 2012a,b;Hamilton et al, 2014;Jutfelt et al, 2013;Munday et al, 2009;Näslund et al, 2015).…”
Section: Introductionmentioning
confidence: 99%